Pengaruh Penggunaan Media Pembelajaran Zoom terhadap Hasil Belajar Fikih Mahasiswa Jurusan Syariah Semester V STIBA Makassar - P., Hamudin; Saat, Sulaiman; Mania, Sitti (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
This study aims to describe the use of zoom learning media, learning motivation, and fiqh learning outcomes, as well as to analyze the effect of using zoom learning media and learning motivation on fiqh learning outcomes for students majoring in sharia in the fifth semester of comparative study program of the Makassar STIBA school, either partially or simultaneously. The type of research in this research is ex post facto that analyzed by descriptive and inferential statistics. The results of study showed that: 1) The use of zoom learning media is in the good enough category. 2) Learning motivation is in the good enough category. 3) Jurisprudence learning outcomes are in the high category. 4) There is an effect of using zoom learning media on fiqh learning outcomes, the effect is 28.4%. This means that in this study 28.4% of the variables of fiqh learning outcomes were influenced by the variable of using zoom learning media and included in the weak but definite category. 5) There is an influence of learning motivation on fiqh learning outcomes, the effect is 17.6%. This means that in this study 17.6% of the fiqh learning outcomes variables were influenced by learning motivation variables and included in the very weak category. 6) There is an effect of using zoom learning media and learning motivation on fiqh learning outcomes for students majoring in sharia in the fifth semester of the Makassar STIBA school of comparison study program, the effect is 8.8%. This means that in this study 8.8% of the variables of fiqh learning outcomes were influenced by the variable use of zoom learning media and learning motivation variables together and included in the very weak category, the rest was influenced by other factors not examined in this study.